2016
DOI: 10.3347/kjp.2016.54.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of <i>Trichomonas vaginalis</i> Diagnosis during Pregnancy at a University Hospital, Argentina

Abstract: The aim of this study was to evaluate different methods for Trichomonas vaginalis diagnosis during pregnancy in order to prevent maternal and perinatal complications. A total of 386 vaginal exudates from pregnant women were analyzed. T. vaginalis was investigated by 3 types of microscopic examinations direct wet mount with physiologic saline solution, prolonged May-Grunwald Giemsa (MGG) staining, and wet mount with sodium-acetate-formalin (SAF)/methylene blue method. PCR for 18S rRNA gene as well as culture in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…In our study, even when the wet preparation was performed at the sample collection site, by the experienced reader who routinely performs the wet preparations at the clinic, its sensitivity (25%) was still poor. Various studies using related but not exactly the same study designs report the sensitivity of WMM to range from around 38 to 65% [4, 11, 18, 23]. Testardini et al reported sensitivity of WMM of 45.8% in all the patients studied but it increased to 87.5% in symptomatic patients but in their study, one millilitre of physiologic saline was used instead three drops [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, even when the wet preparation was performed at the sample collection site, by the experienced reader who routinely performs the wet preparations at the clinic, its sensitivity (25%) was still poor. Various studies using related but not exactly the same study designs report the sensitivity of WMM to range from around 38 to 65% [4, 11, 18, 23]. Testardini et al reported sensitivity of WMM of 45.8% in all the patients studied but it increased to 87.5% in symptomatic patients but in their study, one millilitre of physiologic saline was used instead three drops [4].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of TV infection in this study was 8.6% based on all positive tests. Various studies report different prevalence values ranging from 13 to 41% based on the methods used, study settings, social-demographics and symptomatology of studied populations [ 4 , 9 , 10 ]. In high-risk populations such as female sex workers in sub-Saharan Africa (SSA), the prevalence of active TV infection can be as high as 47% [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the diagnostic methods, the wet mount microscopy is low in cost, but poor in sensitivity [23]. The method of culture T. vaginalis is widely recognized as the "gold standard" for diagnosing trichomoniasis [24]. The sensitivity of the diagnostic method is high, but it takes a long time and requires high quality specimens, and microscopic examiner needs to be professional and experienced.…”
Section: Introductionmentioning
confidence: 99%